The Influence of Digital Marketing and Service Quality on Customer Loyalty (on MSME Entrepreneurship Case Study "Uni Eti Cosmetic Store" in Bandar Lampung) - Daud, Syahril; DK, Angelica Maharani; Imelya, Jingga; Amellia, Monica (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
This study examines the influence of digital marketing and service quality on customer loyalty at Uni Eti Cosmetics Store. Through a quantitative approach and case study, this study analyzes the relationship between the independent variables of digital marketing (X1) and service quality (X2) and the dependent variable of customer loyalty (Y). The results of the study indicate that digital marketing has a significant influence on customer loyalty, while service quality does not show a significant influence. However, simultaneously, digital marketing and service quality have a positive and significant influence on customer loyalty. These findings highlight the importance of an effective digital marketing strategy in attracting and retaining customers, as well as the important role of service quality in creating higher customer satisfaction. This study recommends that Uni Eti Cosmetics Store continue to improve its digital marketing strategy and pay attention to service quality to increase customer loyalty and achieve long-term success.